2019
DOI: 10.1021/acsphotonics.8b01555
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Emission into Nanophotonic Resonators

Abstract: Chiral emission, where the handedness of a transition dipole determines the direction in which a photon is emitted, has recently been observed from atoms and quantum dots coupled to nanophotonic waveguides. Here, we consider the case of chiral light-matter interactions in resonant nanophotonic structures, deriving closed-form expressions for the fundamental quantum electrodynamic quantities that describe these interactions. We show how parameters such as the position dependent, directional Purcell factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 34 publications
(72 reference statements)
1
36
0
Order By: Relevance
“…A promising approach is to exploit chiral quantum optics to form a chiral interface that facilitates the unidirectional transfer of the spin to the guided photons. [27] To date, chiral coupling has been intensively evaluated in various nanophotonic structures including metal surfaces, [28,29] optical fibers, [30,31] semiconductor waveguides, [32][33][34][35] microresonators, [36][37][38][39][40][41][42][43] and topological nanostructures. [44,45] Particularly, the tightly confined light field carries transverse spin angular momentum; thus, a link between the spin and propagation direction of light can be introduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising approach is to exploit chiral quantum optics to form a chiral interface that facilitates the unidirectional transfer of the spin to the guided photons. [27] To date, chiral coupling has been intensively evaluated in various nanophotonic structures including metal surfaces, [28,29] optical fibers, [30,31] semiconductor waveguides, [32][33][34][35] microresonators, [36][37][38][39][40][41][42][43] and topological nanostructures. [44,45] Particularly, the tightly confined light field carries transverse spin angular momentum; thus, a link between the spin and propagation direction of light can be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…To date, chiral coupling has been intensively evaluated in various nanophotonic structures including metal surfaces, [ 28,29 ] optical fibers, [ 30,31 ] semiconductor waveguides, [ 32–35 ] microresonators, [ 36–43 ] and topological nanostructures. [ 44,45 ] Particularly, the tightly confined light field carries transverse spin angular momentum; thus, a link between the spin and propagation direction of light can be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Novel phenomena stemming from asymmetric coupling have been studied theoretically in a range of systems, including spin networks [27], cavity-based photonic devices [28,29], quantum emitters coupled to plasmonic waveguides [30,31], nanophotonic ring resonators [32,33], synthetic phonons [34], and Janus dipoles [35]. Recently, it was shown that chiral coupling at the nanoscale naturally arises in the system of two circularly polarized quantum emitters held above a metal surface, where the surface plasmons mediating the emitteremitter interactions can be controlled in a manifestation of reservoir engineering [36].…”
Section: Introductionmentioning
confidence: 99%
“…A number of associated experiments have been implemented. Besides, this chiral lightmatter interaction between photonic nanostructure and quantum emitter has also been realized in other structures, such as nanobeam waveguides [34,45], optical resonators [46,47], and metamaterials [48]. Here, more details about systematic theoretical research and applications for chiral quantum interface in conventional nanostructures have been reviewed in Ref.…”
Section: Progress In Chiral Quantum Interface and Topological Photonicsmentioning
confidence: 99%